Antimicrobial Resistance in Environmental Waters - Ng, Charmaine (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue on Antimicrobial Resistance in Environmental Waters features 11 articles on the monitoring and surveillance of antimicrobial resistance (AMR) in natural aquatic systems (i.e., reservoirs, rivers), and effluent discharge from water treatment plants to assess the effectiveness of AMR removal and resulting loads in treated waters. Some of the key elements of AMR studies presented in this Special Issue highlight the underlying drivers of AMR contamination in the environment and the evaluation of the hazard imposed on aquatic organisms in receiving environments through ecological risk assessments. As described in this Issue, screening antimicrobial peptide (AMP) libraries for biofilm disruption and antimicrobial candidates are promising avenues for the development of new treatment options to eradicate resistance.